Recent progress in thick‐film organic photovoltaic devices: Materials, devices, and processing - Zhang, Difei; Fan, Baobing; Ying, Lei; Li, Ning; Brabec, Christoph; Huang, Fei; Cao, Yonghai (SusMat, 2021)
A successful transfer of organic photovoltaic technologies from lab to fab has to overcome a range of critical challenges such as developing high-mobility light-harvesting materials, minimizing the upscaling losses, designing advanced solar modules, controlling film quality, decreasing overall cost, and extending long-operation lifetime. To realize large-area devices toward practical applications, much effort has been devoted to understanding the fundamental mechanism of how molecular structures, device architectures, interfacial engineering, and light management and carrier dynamics affect photovoltaic performance. Such studies addressed various fundamental issues of charge carrier behavior in organic heterojunctions primarily in terms of exciton generation dependence upon light incidence, charge transportation dependence on built-in electric field, and charge extraction versus recombination. In consideration of high-throughput roll-to-roll process for large-scale fabrication of organic photovoltaic devices, it is highly appreciable to realize high power conversion efficiencies that are highly tolerable to the film thickness. Herein we summarize the recent progress in developing thick-film organic photovoltaic devices from the perspective of efficiency-loss mechanisms, material design, and device optimization strategies, proposing guidelines for designing high-efficiency thickness-insensitive devices toward mass production.